Best Answer

4x - 3y = -7

Change all signs: -4x + 3y = 7

Add 4x to both sides: 3y = 4x + 7

Divide both sides by 3: y = (4/3)*x + 7/3

m = 4/3, b = 7/3

Q: How do you put 4x - 3y equals -7 in y equals mx plus b form?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-4x + 3y = 9

3y = 4x + 9 -4x + 3y = 9 is the standard form

-2x plus 3y equals 1

4x+3y = 3 3y = -4x+3 y = -4/3x+1 in slope intercept form

9x+3y = 6 3y = -9x+6 y = -3x+2 which is now in slope-intercept form

Related questions

-4x + 3y = 9

3y = 4x + 9 -4x + 3y = 9 is the standard form

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------

3y=4x+9.....-4xAnswer: 4x-3y=9

(2,7)

5x+3y

4.34684352143

5x + 3y = 17 is in its simplest form because there are no alike terms to combine.

4x+3y = 12 3y = -4x+12 y = -4/3x+4

-2x plus 3y equals 1

7x + 3y = 42 can be converted to slope intercept form using the formula y = mx + b. First, get 3y on to the outside. -3y = 7x - 42 Divide everything by -3. You are left with y = 7/3x + 14

The equation for 3y + 3y = -1 is 3y + 3y = -1.